E-Risk Governance: Model Tata Kelola Risiko pada Lembaga Pendidikan Modern - Putri Utami; Irsyad, Irsyad; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2025)
This article discusses the application of E-Risk Governance as a modern risk governance model for educational institutions. This study aims to explain key concepts, urgency, and the implementation structure of digital-based risk governance to improve organizational resilience and decision-making quality. The analysis uses a qualitative descriptive approach by synthesizing research from experts in education management and risk governance. The results show that E-Risk Governance supports transparency, strengthens risk identification, and enhances mitigation through integrated digital systems. This model is highly relevant for modern educational institutions facing dynamic operational, technological, and strategic risks.